ChemInform Abstract: A Pd‐Based Regioselective Strategy to Indole‐1, 2‐fused 8‐ and 9‐Membered Rings: Their Evaluation as Potential Scaffolds for Apoptosis in Zebrafish. Issue 43 (21st October 2014) - Prasad, Bagineni; Sreenivas, B. Yogi; Sushma, Araka; Yellanki, Swapna; Medisetti, Raghavender; Kulkarni, Pushkar; Pal, Manojit
Abstract A strategy based on Pd‐mediated intramolecular endo‐trig ring closure of 1, 2‐disubstituted indoles leading to indole‐1, 2‐fused 8‐ and 9‐membered rings is described.